Small Modular Reactors as a Means of Ensuring the Energy Independence of Business and a Tool for Decarbonization of Ukrainian Energy Sector - Banshchykov Petro H.; Vostriakov Oleksandr V.; Barabas Dmytro O.; Stepura Denys F. (Problemi Ekonomiki)
At the time of the systematic strikes of the aggressor state on the energy infrastructure of Ukraine, the issues of ensuring the energy independence of domestic business organizations become especially relevant. The problematic of reducing greenhouse gas emissions remains important. A promising direction for solving these problems is the use of small modular reactors. Specialized scientific studies devoted to the technical and economic feasibility study of small modular reactor operation projects do not summarize the most relevant areas of their use as a tool for ensuring the energy independence of business and decarbonization of the economy in the context of achieving Ukraine’s environmental goals. They also lack comprehensive consideration of significant technical and economic parameters of small modular reactor projects when predicting their efficiency and competitiveness in relation to other energy sources. The article is aimed at systematizing the advantages and disadvantages of the introduction of small modular reactors as a tool for ensuring energy independence of business and decarbonization of the energy sector of Ukraine with closer defining of the economic aspects of their operation in Ukrainian realities. The article summarizes the expected advantages and disadvantages of using small modular reactors. The relevant analysis showed the pertinence and urgency for Ukraine of deploying a network of small modular reactors of a modern level protected from missile attacks and artillery shellings. Problems and gaps in the existing methodological support for assessing the economic efficiency of small modular reactor projects are outlined. The growth of energy needs of mankind and the accumulation of environmental problems in the operation of traditional power plants force research teams in many countries to develop methodological tools for assessing the economic efficiency and competitiveness of small modular reactor projects, to implement and improve pilot projects that will provide consumers with affordable and safe energy sources in the future.